2017
DOI: 10.3892/etm.2017.4917
|View full text |Cite
|
Sign up to set email alerts
|

Novel targeted puncture technique for percutaneous transforaminal endoscopic lumbar discectomy reduces X-ray exposure

Abstract: The present study explored a method to reduce X-ray exposure dose and avoid targeted puncture complications in percutaneous transforaminal endoscopic lumbar discectomy (PTELD). A total of 66 patients with lumbar disc herniation were divided into two groups for a controlled study. In the experimental group, 31 patients were subjected to PTELD using a novel targeted puncture technique with application of a lumbar disc herniation target collimator. The remaining 35 patients in the control group were subjected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The recurrent disc herniation rate experienced in this study is similar to other studies in the literature which have reported reherniation rates of 6-12.5% after TELD (22,23). Some recent studies assessing the transforaminal endoscopic technique have reported reherniation rates as low as a 0.5% (16,24). This study attempts to analyze characteristics of patients who had experienced recurrent disc herniations after TELD.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The recurrent disc herniation rate experienced in this study is similar to other studies in the literature which have reported reherniation rates of 6-12.5% after TELD (22,23). Some recent studies assessing the transforaminal endoscopic technique have reported reherniation rates as low as a 0.5% (16,24). This study attempts to analyze characteristics of patients who had experienced recurrent disc herniations after TELD.…”
Section: Discussionsupporting
confidence: 85%
“…The surgical procedure of transforaminal endoscopic lumbar decompression (TELD) has the benefits of an ultraminimally invasive spine surgery including small incision, faster recovery, less need for pain medications, and lower blood loss while still achieving equally effective pain reduction compared to traditional open surgical techniques (11)(12)(13)(14)(15). TELD does not affect spinal stability and forms minimal scar adhesions (13,16). This technique has gained increasing popularity as patient demand for more minimally invasive approaches has grown.…”
Section: Introductionmentioning
confidence: 99%
“…6,18,19 This is likely due to the associated reduced muscle injury and bleeding, diminished scar formation in the spinal canal, and relatively short hospital stay. [5][6][7][8]20,21 In total, 148 cases of LDH, who were treated with PETD, were analyzed in this study. The VAS and ODI scores of all patients improved significantly at each follow-up, compared to the preoperative values (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] The main advantages of PELD include local anesthesia, minimal tissue destruction, favorable outcomes, rapid recovery, and minimal invasion. [5][6][7][8] Although prior investigations revealed that PELD achieves satisfactory clinical efficacy, 2,[4][5][6][7][8] literature reports and our own experiences revealed that a small number of patients still suffer from pain and disability after PELD, and some patients even require secondary surgery. [9][10][11][12] The Sang study reported that following PELD, 9.6% patients undergo revision surgery on the same segment, and 26.6% undergo revision surgery on other segments.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its numerous advantages, PELD is technically challenging and has a steep learning curve[ 11 , 12 ]. Accurate puncturing and working channel intubation are required to create favorable conditions for endoscopic surgery[ 13 , 14 ]. However, the puncture technique is relatively difficult, especially in percutaneous transforaminal endoscopic lumbar discectomy (PTELD), which requires specific puncture angles to certain parts of the intervertebral foramen.…”
Section: Introductionmentioning
confidence: 99%